Palladium-catalyzed enantioselective three-component synthesis of α-arylglycine derivatives from glyoxylic acid, sulfonamides and aryltrifluoroborates - Jakob, Bastian; Schneider, Nico; Gengenbach, Luca; Manolikakes, Georg (Beilstein Journal of Organic Chemistry, 2023)
A palladium-catalyzed enantioselective three-component reaction of glyoxylic acid, sulfonamides and aryltrifluoroborates is described. This process provides modular access to the important α-arylglycine motif in moderate to good yields and enantioselectivies. The formed α-arylglycine products constitute useful building blocks for the synthesis of peptides or arylglycine-containing natural products.
Keywords: amino acids; asymmetric catalysis; multicomponent reaction; palladium catalysis; Petasis reaction; sulfonamides